Polyploidy in Orchid Breeding, Advances and Perspectives - Bolaños Villegas, Pablo Alberto (2022)
The orchid market is a dynamic horticultural business in which novelty and beauty command high prices. The development of miniature to large and showy flowers, in addition to fragrance, is mainly of interest. Overall organ size might be modified by doubling the chromosome number, which can be accomplished by careful study of meiotic chromosome disjunction in hybrids or species. Meiosis is the process in which diploid (2n) pollen mother cells recombine their DNA sequences and then undergo two rounds of division to give rise to four haploid (n) cells called sporads. Thus, by interfering in chromosome segregation, one can induce the development of diploid recombinant sporads called dyads. These dyads may be used for breeding polyploid progenies with enhanced fertility and large flower size. This review gives an overview of developments in orchid breeding placed in the large context of ploidy breeding in higher plants to facilitate innovation.